Ecomparism, sebuah konsep perencanaan wisata Pantai Teloek Dalam – Bintan, Provinsi Kepulauan Riau - Putra, Ridwansyah Trisnanda; Ramadanti, Pitria; Thoifur, Dimas Muhammad; Hestiningsih, Hindun; Ramadhan, Risalah Rabbani; Syahadat, Ray March; Putra, Priambudi Trie (Jurnal Arsitektur Lansekap; Vol.4, No.2, Oktober 2018, 2018)
Ecomparism, a Concept for Tourism Planning of Teloek Dalam Beach – Bintan, Province of Kepulauan Riau. The aim of this planning was to create an ecological tourism landscape that remains compact at Teloek Dalam Beach. In this case compact means complete in term of harmonizing the man-made and natural landscape to support various activities both on the terrestrial and aquatic. The analysis used included some aspects such as environmental, visual, social, ecosystem, vegetation, animals, willingness to pay, carrying capacity, and environmental quality assessment. The results show that the visual aspect is quite good with feature of white sands, blue sea, and sunrise. There are 23 species of animals, 9 species of seagrass, and 3 dominate species of coastal vegetation. The carrying capacity for this site is 12.493 people. With average 4 hours visit time, the assumption used can only accommodate visitors every four hours for 3.123 people and 9.370 visitors staying. The concept of ecomparism is a concept of tourism landscape planning that does not exclude ecological principles despite creating compact area planning. The planning results from three concepts of space which are divided into core, buffer, and utilization zones. The utilization zone is divided into 6 spaces based on 13 activities.